Highly active electron-deficient Pd clusters on N-doped active carbon for aromatic ring hydrogenation. Issue 6 (9th November 2015) - Nie, Renfeng; Jiang, Hezhan; Lu, Xinhuan; Zhou, Dan; Xia, Qinghua
Abstract : Pyridinic nitrogen species in N-doped active carbon ( x N-AC) are responsible for high activity of ring hydrogenation via the formation of a high percentage of electron-deficient Pd clusters. Abstract : N-doped active carbon (N-AC) has been synthesized via heat treatment of a mixture consisting of dicyandiamide as the nitrogen source and commercial active carbon as the precursor. This material is especially adapted for anchoring ultrafine Pd nanoparticles by a very clean strategy using H2 as the reductant. The physicochemical properties of materials were investigated by powder X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The results reveal that the variation of the treatment temperature can assist the tuning of the content of N and the dispersion of Pd on x N-AC, by which Pd nanoparticles with a narrow size distribution centered at around 1.8 nm can be obtained. These robust catalysts show very high catalytic activity for the aromatic ring hydrogenation of acidic substrates, such as electron-deficient benzoic acid or electron-rich phenol, under mild conditions in aqueous media. Excellent catalytic results (9.2 times higher activity in comparison to non-doped catalyst for benzoic acid hydrogenation), high stability and easy recyclability of the catalyst were achieved. The strong interaction between the pyridinic nitrogen group and Pd species will lower the reducibility of the Pd species and result in the formation of relatively electron-deficient and ultra-small sized Pd clusters, thus leading to high hydrogenation activity.